2013
DOI: 10.1371/journal.pone.0061744
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Effects Modelling of Scale Growth Profiles Predicts the Occurrence of Early and Late Fish Migrants

Abstract: Fish growth is commonly used as a proxy for fitness but this is only valid if individual growth variation can be interpreted in relation to conspecifics' performance. Unfortunately, assessing individual variation in growth rates is problematic under natural conditions because subjects typically need to be marked, repeated measurements of body size are difficult to obtain in the field, and recaptures may be limited to a few time events which will generally vary among individuals. The analysis of consecutive gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 73 publications
(68 reference statements)
1
18
0
Order By: Relevance
“…The longitudinal mixed-effects model design accounted for correlations of repeated measures within an individual by treating each individual as a random effect (Singer and Willett 2009;Cheng et al 2010;Marco-Rius et al 2013). We found curvilinear relationships between ages and growth (Fig.…”
Section: Statistical Analysesmentioning
confidence: 84%
See 1 more Smart Citation
“…The longitudinal mixed-effects model design accounted for correlations of repeated measures within an individual by treating each individual as a random effect (Singer and Willett 2009;Cheng et al 2010;Marco-Rius et al 2013). We found curvilinear relationships between ages and growth (Fig.…”
Section: Statistical Analysesmentioning
confidence: 84%
“…Although a relationship between salmon scale radius size and fish length has been well established in the literature (e.g., Marr 1943;Ricker 1973Ricker , 1976, in common with many other studies (e.g., McCarthy et al 2008;Hogan and Friedland 2010;Marco-Rius et al 2013), scale sizes were not converted to body length or mass estimates, as it would introduce additional errors as a result of (i) scale reabsorption of the final annuli during the final year reducing accuracy (Seo et al 2006) and (ii) uncertainty in the relationship between scale growth to body growth. Scale radius was correlated with fork length (Pearson r = 0.47, p < 0.001; fish length data available from 1998 to 2010).…”
Section: Scale Analysismentioning
confidence: 90%
“…), (ii) number of scale growth circuli during the first winter, (iii) scale intercirculi spacing during the first winter, and (iv) scale radius at the end of the first winter, as detailed in Marco‐Rius et al. (, ). Analysis of scale growth circuli can be used to reconstruct and compare growth profiles of individuals of different ages and has previously been used to assess variation in growth performance of invasive trout in the area (Schröder and Garcia de Leaniz ).…”
Section: Methodsmentioning
confidence: 99%
“…Repeatabilities for the other scale traits were not calculated as we had previously found that these were similarly high in brown trout (Marco‐Rius et al. , ).…”
Section: Methodsmentioning
confidence: 99%
“…This method has commonly been used for species in temperate regions where the intraannual variations in the environment favour the record of these marks (Marco-Ruis, Caballero, Morán, & García-de Leaniz, 2013).…”
Section: Inter-cohort Growth For Three Tropical Resources: Tilapia Omentioning
confidence: 99%